Older adolescents and young adults willingness to receive the COVID-19 vaccine: Implications for informing public health strategies. Issue 26 (11th June 2021) - Afifi, Tracie O.; Salmon, Samantha; Taillieu, Tamara; Stewart-Tufescu, Ashley; Fortier, Janique; Driedger, S. Michelle
Highlights: 65.4% of the sample indicated a willingness to get a COVID-19 vaccine. Sociodemographic factors, health, and COVID-19 knowledge were related to vaccine willingness. Adversity history was related to vaccine willingness. Sex differences in reasons for vaccine hesitancy were noted. Public health messaging: vaccine safety, how it works, importance of not becoming infected. Abstract: Importance: The success in ending the COVID-19 pandemic rests partly on the mass uptake of the COVID-19 vaccine. Little work has been done to understand vaccine willingness among older adolescents and young adults. This is important since this age group may be less likely to adhere to public health guidelines. Objective: To understand willingness of getting a vaccine and reasons for vaccine hesitancy among a sample of older adolescents and young adults. Design: Data were from the Well-Being and Experiences study (The WE Study), a longitudinal community-based sample of older adolescents and young adults collected from Winnipeg, Manitoba, Canada from 2017 to 2020 (n = 664). Setting: The study setting was a community-based observational longitudinal study. Participants: Participants for the study were aged 14 to 17 years old at baseline in 2016–17 (n = 1000). Data were also collected on one parent/caregiver. Waves 2 (n = 747) and 3 (n = 664) were collected in 2019 and 2020, respectively. Exposures: The main exposures were sociodemographic factors, health conditions, COVID-19 knowledge, and adversity history. Main Outcomes: The main outcomes were COVID-19 vaccine willingness, hesitancy, and reasons for hesitancy. Results: Willingness to get a COVID-19 vaccine was 65.4%. Willingness did not differ by age, sex, or mental health conditions, but did differ for other sociodemographic characteristics, physical health conditions, COVID-19 knowledge, practicing social/physical distancing, and adversity history. The most common reasons for not wanting a vaccine were related to safety, knowledge, and effectiveness. Sex differences were noted. Conclusions and Relevance: Increasing uptake of the COVID-19 vaccine among older adolescents and young adults may rely on targeting individuals from households with lower income, financial burden, and adversity history, and generating public health messaging specifically aimed at vaccine safety, how it works to protect against illness, and why it is important to protect oneself against a COVID-19 infection.